Graphene material preparation through thermal treatment of graphite oxide electrochemically synthesized in aqueous sulfuric acid. Issue 32 (4th April 2017) - Gurzęda, B.; Buchwald, T.; Nocuń, M.; Bąkowicz, A.; Krawczyk, P.
Abstract : The present work demonstrates a simple and low-cost method to produce bulk quantities of graphene material through the thermal treatment of graphite oxide (GO). Abstract : The present work demonstrates a simple and low-cost method to produce bulk quantities of graphene material through the thermal treatment of graphite oxide (GO). GO of a high oxidation degree was synthesized by electrochemical overoxidation of natural graphite in 11 M H2 SO4 using linear sweep voltammetry (LSV) technique. The thus synthesized GO was thermally exfoliated-reduced at 500 °C in air, giving the final product – thermally reduced graphite oxide (TRGO). It should be emphasized that the process of TRGO formation from electrochemically obtained GO is for the first time described in the present work. Due to shock treatment, the BET specific surface area of TRGO increased from 4 to 455 m 2 g −1 . Additionally, a decrease in the concentration of oxygen functionalities was also observed. Thermal stability of electrochemically synthesized GO was investigated by thermogravimetric analysis (TGA). In order to characterize the synthesized TRGO, investigations by X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) were performed.